2006
DOI: 10.1080/07481180600848322
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Bonds and Reconstructing Meaning: Mitigating Complications in Bereavement

Abstract: Drawing on attachment theory and constructivist conceptualizations of bereavement, the authors assessed the relation between continuing bonds coping and meaning reconstruction following the death of a loved one and complicated grief symptomatology. Five hundred six young adults in the first two years of bereavement from a variety of losses completed the Inventory of Complicated Grief along with measures of the strength of their ongoing attachment to the deceased and their capacity to make sense of the loss, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
287
1
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 358 publications
(317 citation statements)
references
References 36 publications
16
287
1
13
Order By: Relevance
“…Continued connections to the deceased can, for some persons, encourage increased spirituality or a desire to maintain spiritual beliefs (Cait, 2004;Sormanti & August, 1997); with the deepening of spirituality representing spiritual growth. A caveat, however, is that the continued connection with the deceased may or may not be generally adaptive (Neimeyer, Baldwin, & Gillies, 2006;Parker, 2005;Stroebe & Schut, 2005).…”
Section: Grief and Posttraumatic Growthmentioning
confidence: 99%
“…Continued connections to the deceased can, for some persons, encourage increased spirituality or a desire to maintain spiritual beliefs (Cait, 2004;Sormanti & August, 1997); with the deepening of spirituality representing spiritual growth. A caveat, however, is that the continued connection with the deceased may or may not be generally adaptive (Neimeyer, Baldwin, & Gillies, 2006;Parker, 2005;Stroebe & Schut, 2005).…”
Section: Grief and Posttraumatic Growthmentioning
confidence: 99%
“…18, 138). Specifically, inclusion of T1 outcome scores was imperative to our repeated-measures, within-subjects design; inclusion of Contact was based on prior research showing that pre-death levels of contact between bereaved individuals and their deceased loved one specifically predicted CG [28]; [61]; and, TSL was included because of the relatively great variation between participants in terms of post-loss duration. Table 1 summarizes the descriptive statistics for the background variables, religious coping, and bereavement distress measures used in this study.…”
Section: Data Analysis Planmentioning
confidence: 99%
“…For example, previous studies have suggested that risk factors for PGD, including that of violent loss, increase symptoms of PGD by hindering meaning making such that the bereft are unable to ‘make sense’ of the death or its aftermath (Milman, Neimeyer, Fitzpatrick, MacKinnon, Muis, & Cohen, under review; Currier, Holland, Coleman, & Neimeyer, 2007; Lichtenthal, Neimeyer, Currier, Roberts, & Jordan, 2013; Neimeyer, Baldwin, & Gillies, 2006; Rozalski, Holland, & Neimeyer, 2017). Building on this research, this study examines which themes of meaning are disrupted specifically following violent loss with the aim of informing preventive interventions that facilitate meaning making in a manner that mitigates symptoms of PGD among the violently bereft.…”
mentioning
confidence: 99%